Utilizing the Qualitative Content Analysis Approach to Present a Psychological Maturity Model for Research Managers Based on Entrepreneurial Development in Education-Oriented Organizations - Bayati, Zahra; Jafari Kalarijani, Seyyed Ahmad; Mehrara, Asadollah; Gholipour Kanani, Yosef (Management Strategies and Engineering Sciences, 2024)
Human resources with psychological maturity are among the essential assets required for fostering entrepreneurship in education-oriented organizations. When coupled with high-level professional skills, they become an unrivaled asset for these organizations and serve as the most critical potential factor for transformation, modernization, and the continued effectiveness of production, service, and educational sectors of society. This study aimed to present a psychological maturity model for research managers based on entrepreneurial development in education-oriented organizations. The statistical population consisted of experts, managers of education-oriented organizations, and university professors who have conducted research in the field of entrepreneurial development. The sampling method employed was the snowball sampling technique, leading to the selection of 15 experts. Data were collected using open-ended interviews and analyzed using the qualitative content analysis technique. Following open coding, axial coding, and categorization, several dimensions of psychological maturity were identified and introduced. Personal maturity includes components of psychological readiness and professional capabilities. Entrepreneurial cultural maturity consists of motivations related to entrepreneurship, as well as beliefs and individual values concerning entrepreneurship. Entrepreneurial interaction maturity encompasses verbal communication skills, non-verbal communication skills, listening skills, writing skills, presentation skills, networking skills, and conflict resolution skills. Entrepreneurial psychological encouragement involves components of encouragement toward entrepreneurial behavior and psychological self-leadership.